STRATEGI PENGEMBANGAN USAHA SAYURAN BERBASIS PERTANIAN ORGANIK - Eri Arodi Sefi; Charles Kapioru; Made Tusan Surayasa (Buletin Ilmiah Impas, 2022)
The purpose of this study is to identify internal and external factors that influence the development of organic vegetable farming, to analyze alternative strategies in the development of organic agriculture, and to determine priority strategies in the development of organic vegetable farming. The location of this research was carried out with the consideration of CV. PPO is one of the places that produce and provide organic agricultural products in Kupang Regency and Kupang City. Primary data obtained from direct observation, discussion and interviews with respondents, secondary data obtained from books, journals, papers, BPS. The data analysis used to answer the objectives are IFE matrix analysis, EFE matrix analysis, IE matrix analysis, SWOT matrix analysis and QSP matrix analysis. (1) The results showed 10 strength factors, 7 weakness factors, 6 opportunity factors and 6 threat factors. (2) The results of the IFE matrix calculation show that the total score of the strength factor is 2.234 and the total score of the weakness factor is 0.702, which means that the influence of the strength factor is greater than the influence of the weakness factor on the business development of organic vegetables. While the results of the EFE matrix calculation show that the total score of the opportunity factor is 1.805 and the total score of the threat factor is 0.769, which means that the influence of the opportunity factor is greater than the threat factor on the development of the organic vegetable business. (3) In the IE matrix the position of CV PPO is in quadrant I which means that CV PPO is strong and has a chance. The strategy given is Aggressive, where there are strengths that are used to seize profitable opportunities. (4) The SWOT matrix analysis produces 6 strategies, namely creating attractive product packaging so that they can compete with other agricultural products, adopting green house agricultural technology to overcome climate influences, creating more strategic marketing places, maximizing facilities, capital and land certification and products that are exists in producing and meeting market demand, taking advantage of P4S opportunities to increase public awareness and creating a wider market, Optimizing the use of internet services to expand product marketing. (5) The QSP matrix analysis resulted in a strategy of creating attractive product packaging in order to compete with other agricultural products with a total score of 5,653 which is a priority strategy.